A Concept Analysis of Personalized Health Care in Nursing. Issue 1 (26th January 2015) - Han, Claire Jungyoun
Abstract : Purpose: The purpose of the study is to identify the concept of personalized health care in nursing and to address future direction in person‐centered nursing care. Background: Personalized health care has attracted increased attention in the twenty‐first century. As more and more preclinical studies are focusing on cost‐effective and patient‐centered care, there also has been an identified need for a personalized health care in nursing. Yet the term lacks clear definition and interests among healthcare professionals. Review Methods: Rodgers' strategy for concept analysis was used in this analysis. A literature review for 1960–2014 was conducted for the following keywords: nursing care, personalized, and health care. Results: The analysis demonstrates that personalized health care in nursing is an intangible asset, including explicit attributes (interprofessional collaboration and individualized care approach) and implicit attributes (managing personal vulnerabilities: molecular‐based health information and self‐health‐seeking behaviors). The result of this analysis provides a guide for further conceptual and empirical research and clinical practice in the personalized healthcare era. Conclusion: This concept analysis represents an effort to describe the attributes of a concept regarded as representing an important feature of nursing care and to promote discourse that will enhance maturation of the concept into one that is established with clearly delineated characteristics.